Maternal and Foetal Outcome of Eclampsia in Mymensingh Medical College Hospital (Journal of Shaheed Suhrawardy Medical College, 2012)
This prospective cross-sectional study is undertaken to evaluate the maternal and foetal outcome of patients admitted in Mymensingh Medical College Hospital from November 2002 to April 2003. Among 5175 obstetric patients admitted to the hospital, 212 were eclamptic, yielding an incidence of 4.1%. The antepartum, intrapartum and postpartum incidences of eclampsia were 50%, 26.5% and 23.5% respectively. Among the patients with eclampsia, 56.85% had good prognosis without any added complication and 45.85% had complications. The case fatality rate of eclampsia was 5%, which was lower than that of the previous studies. In this study out of 200 patients, foetal death was 23.98%. Changing the ante convulsant from diazepam to magnesium sulfate the incidence of death in eclampsia patients have significantly reduced. But reduction of the risk of death was difficult when patients had developed complications. Most of the patient who died was in complicated group, these complications developed as a result of a delayed treatment. Therefore, efforts should be directed at developing awareness to receive treatment at an appropriate time to reduce the mortality from eclampsia and its complications. DOI: http://dx.doi.org/10.3329/jssmc.v1i1.12169 Journal of Shaheed Suhrawardy Medical College Vol.1, No.1, December 2009 p.14-17